The impact of agricultural manufacturing on the added value of agricultural products (legume processing) in Lattakia - جنيد رند (Submission and Review of Research -Biological Sciences Series, 2025)
The research aims to study the added value of legume manufacturing in Lattakia. The descriptive analytical approach was adopted, and several analytical methods were used, such as the arithmetic mean and time trend equations. The results showed that the change in the quantity of canned produce in recent years has been a positive change towards increasing at varying rates. This was confirmed by the time trend equation for the years (2005-2020), which showed a positive trend with a decline at the beginning of 2011, followed by a rise at the beginning of 2013. This increase in production can be attributed to several factors, most notably the development of applied technologies in manufacturing and the increase in local demand for canned products due to changing lifestyles. A decline was observed in the contribution of the food industry sector to employment at the beginning of 2015, as a negative change was recorded in the contribution rate (3.2), before it began to recover. In 2020, a contribution rate of 30% of the workforce in the public sector for manufacturing industries was recorded. In the context of the manufacturing efficiency study, recent data for 2023 from Al-Sindyan Company for analyzing economic indicators for legume manufacturing was adopted to provide a current picture of the reality of agricultural manufacturing. The net added value for chickpea manufacturing was recorded at 7,018 thousand Syrian pounds per ton, for fava beans at 8,765 thousand Syrian pounds per ton, and for beans at approximately 4,701 thousand Syrian pounds per ton. There is an increase in the cost of packaging and wrapping relative to the total costs.